A Retrospective Review of CyberKnife Stereotactic Body Radiotherapy for Adrenal Tumors (Primary and Metastatic): Winthrop University Hospital Experience - Desai, Amishi; Rai, Hema; Haas, Jonathan; Witten, Matthew; Blacksburg, Seth; Schneider, Jeffrey G. (Frontiers in Oncology, 2015)
The adrenal gland is a common site of cancer metastasis. Surgery remains a mainstay of treatment for solitary adrenal metastasis. For patients who cannot undergo surgery, radiation is an alternative option. Stereotactic body radiotherapy (SBRT) is an ablative treatment option allowing larger doses to be delivered over a shorter period of time. In this study, we report on our experience with the use of SBRT to treat adrenal metastases using Cyberknife technology. We retrospectively reviewed, the Winthrop-University radiation oncology data base to identify 14 patients for whom SBRT was administered to treat malignant adrenal disease. Of the factors examined, the biologic equivalent dose (BED) of radiation delivered was found to be the most important predictor of local adrenal tumor control. We conclude that CyberKnife-based SBRT is a safe, non-invasive modality that has broadened the therapeutic options for the treatment of isolated adrenal metastases.